The Effect of Supplementation of Diet with Vitamin-E and Selenium and their Combinations on the Performance and Lipid Profiles of Layer Chickens - G. KANCHANA,; G.P JEYANTHI, (International Journal of Pharma and Bio Sciences, 2010)
A biological experiment was conducted to study the effect of vitamin E and selenium supplementation on growth performance and lipid profile with two hundred and ten commercial straight run day-older layer chicks. The chicks were randomly allotted into seven treatment groups with three replicates of ten chicks each. The chicks were fed basal diet (T1), basal diet with 100mg/kg vitamin E (T2), basal diet with 200mg/kg vitamin E (T3), basal diet with 0.2mg/kg selenium (T4), basal diet with 0.4mg/kg selenium (T5), basal diet with 100mg/kg vitamin E plus 0.2mg/kg selenium (T6), and basal diet with 200mg/kg vitamin E plus 0.4mg/kg selenium (T7) for thirty two weeks period. The results revealed that there was no significant difference in body weight of layer chicks for the first four weeks between treatment groups but the body weight of groups (T6 and T7) receiving both vitamin E and selenium supplementation is significantly increased (P<0.05) during 5-32 weeks period of age. The feed intake of layer chicks did not vary significantly between treatment groups. Chicks receiving supplements of both vitamin E and selenium produced significantly (P<0.01) lower total cholesterol, triglycerides, VLDL and LDL cholesterol and significantly higher (P<0.01) HDL cholesterol. Present research suggested that vitamin E and selenium influences lipid metabolism by decrasing total cholesterol, triglycerides, VLDL and LDL cholesterol and increasing HDL cholesterol.